Formal specification of design pattern combination using BPSL - Taibi, T (2003)
Pattern users are faced with difficulties in understanding when and how to use the increasing number of available design patterns due the inherent ambiguity in the existing means (textual and graphical) of describing them. Since patterns are seldom used in isolation but are usually combined to solve complex problems, the above-mentioned difficulties have even worsen.